Clinical course and features of the diagnosis of infectious endocarditis in the elderly - M. A. Stepchenko; N. S. Meshcherina; E. M. Hardikova; M. I. Moskalyuk; I. O. Maltseva (Медицинский вестник Юга России, 2022)
Infectious endocarditis is a formidable disease characterized by an extremely unfavorable prognosis in its natural course. Analyzing the literature data, it can be noted that the frequency of infectious endocarditis in the Russian Federation has relatively high prevalence rates in relation to other countries. Currently, the problem of early diagnosis of infectious endocarditis remains relevant. Despite the fact that the diagnosis of infectious endocarditis has improved, mainly as a result of the improvement of echocardiographic and microbiological approaches, the introduction of new antibacterial drugs and cardiac surgery technologies into clinical practice, the clinical picture, changes in laboratory parameters can lead to the exclusion of immuno-inflammatory, rheumatic, oncological, hematological diseases, complicating and delaying the diagnosis of infectious endocarditis. The first clinical signs of infectious endocarditis may be nonspecific, and the disease remains unrecognized for weeks or even months. The high frequency of thrombotic, thrombohemorrhagic complications indicates profound changes in the hemostasis system in infectious endocarditis and the need to disclose the pathogenesis of these disorders. The combination of these factors led to the late diagnosis of this disease in the patient. The aim of the study is to study the possibility of improving the results of diagnosis and therapy of patients with infectious endocarditis in clinical practice.